Perbandingan Efektivitas Metode Maserasi, Digesti, dan Sokletasi terhadap Nilai Konsentrasi Larutan Stok Ekstrak Daun Singkong (Manihot esculenta Crantz) - Nieyan, Putri Ananda; Hakiki, Salsabila Sofia; Rahim, Audy Nasyiah; Azizah, Anis; Nurrahmah, Salsabila; Herayati; Saputra, Iwan Syahjok (Journal of Chemistry Sciences and Education, 2025)
Cassava leaves (Manihot esculenta Crantz) are known to contain various bioactive compounds such as flavonoids, tannins, saponins, and alkaloids. This study aimed to compare the effectiveness of three extraction methods maceration, digestion, and Soxhlet extraction in producing stock solutions of cassava leaf extract. A total of 5 grams of cassava leaf simplicia was extracted using methanol 96% (maceration), distilled water (digestion), and methanol 99.9% (Soxhlet). The extract yield was measured by evaporating 1 mL of filtrate and weighing the residue. The results showed that the Soxhlet method produced the highest concentration of 0.085%, followed by digestion (0.0132%) and maceration (0.0106%). Soxhlet extraction was more effective due to its continuous solvent circulation at elevated temperatures and higher solvent volume, resulting in a more efficient extraction of active compounds from the cassava leaves.